Williams syndrome deficits in visual spatial processing linked to GTF2IRD1 and GTF2I on Chromosome 7q11.23 - Hirota, Hamao; Matsuoka, Rumiko; Chen, Xiao-Ning; Salandanan, Lora S.; Lincoln, Alan; Rose, Fredric E.; Sunahara, Mariko; Osawa, Makiko; Bellugi, Ursula; Korenberg, Julie R. (Genetics in medicine, 2003)
To identify the relationship between specific genes and phenotypic features of Williams syndrome. Subjects were selected based on their deletion status determined by fluorescence in situ hybridization using a panel of 24 BACs and cosmids spanning the region commonly deleted and single gene analysis using Southern blotting. From the cohort of subjects, three had atypical deletions. Physical examinations and cognitive tests were administered to the three subjects and the results were compared to those from a cohort of typical WS subjects. The molecular results indicate smaller deletions for each subject. In all three cases, typical Williams facies were absent and visual spatial abilities were above that of full deletion WS subjects, particularly in the qualitative aspects of visual spatial processing. Combining the molecular analysis with the cognitive results suggest that the genes GTF2IRD1 and GTF2I contribute to deficits on visual spatial functioning.